The Role of Cartilage-perichondrium Tympanoplasty in the Treatment of Tympanic Membrane Retractions: Systematic Review of the Literature - Angelo Immordino; Federico Sireci; Francesco Lorusso; Francesco Martines; Francesco Dispenza (International Archives of Otorhinolaryngology, 2022)
Introduction Tympanic retraction is a condition characterized by the displacement of the tympanic membrane toward the structures of the middle ear. Clinically, tympanic retractions can lead to hearing loss, ear discharge and/or ear pain. In most of the cases, however, tympanic retractions are asymptomatic and are found accidentally during an ear, nose, and throat (ENT) examination. This condition has created numerous debates regarding the optimal choice of treatment, especially in the asymptomatic forms. The main controversy is regarding the relationship between retraction and the development of cholesteatoma, which would justify a surgical intervention performed for preventive purposes. Objectives To study the effectiveness of cartilage tympanoplasty in the management of tympanic membrane retractions by analyzing the results of the studies conducted on the use of cartilage as a reconstruction material. Data Synthesis A literature review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses group (PRISMA). Study selection, data extraction, and quality assessment were conducted independently by two reviewers. Our initial literature search yielded 2,258 references. Applying the PRISMA flow chart, 1,415 duplicates were excluded, and the remaining 843 abstracts were examined. Afterwards, 794 articles were excluded based on the research protocol criteria. Only 8 papers were included in the review by applying the inclusion and exclusion criteria. Conclusions Despite the limitations of the studies taken into consideration, we can conclude that cartilage tympanoplasty may successfully rehabilitate the atelectatic ear especially in the more advanced stages of retraction, unlike the conservative strategies.